The unsteady simulation for turbulent cavitating flow around a hydrofoil at a low angle of attack - Kie OKABAYASHI; Takuya INAOKA; Wenyang LUO; Takeo KAJISHIMA (Nihon Kikai Gakkai ronbunshu, 2019)
Large-eddy simulation (LES) of the cavitating turbulent flow around a hydrofoil was conducted. Especially, we focused on the improvement of the reproducibility of the hydrofoil performance under the condition of cavitation when considering the unsteadiness of the flow field sufficiently by LES. The analysis object is the cavitating turbulent flow around a Clark-Y11.7% hydrofoil at the angle-of-attack of 2 degrees. The weak compressibility was taken into account in the governing equation. The cavitation is represented by the cavity source based on the homogeneous fluid model. For LES, the subgrid scale (SGS) eddy viscosity was determined by solving the transport equation of SGS kinetic energy. Typical patterns of cavitation that was observed experimentally for various cavitation number were successfully reproduced: e.g., attached sheet cavitation of steady as well as unsteady modes. The reproducibility of the cavitation characteristics of the hydrofoil was improved in comparison with that by previous Reynolds-averaged turbulence models. In addition, by reducing the cavitation number, the slight increase of lift coefficient was observed before the breakdown. These are due to the streamline curvature around the sheet cavity. We found this feature is related to the unsteady motion of large-scale spanwise vortices. LES revealed that the vortices are intermittently generated by the baroclinic torque originated from the onset of sheet cavitation.